2019
DOI: 10.24099/vet.arhiv.0338
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac, respiratory and thermoregulation parameters following graded exercises in Lipizzaner horses

Abstract: The sport results or exercise achievements of Lipizzaner horses are rarely considered, as their involvement in equestrian sports is rare. As a result, norms for evaluation of their fitness level during training or performance have not yet been determined. The aim of this study was to determine the basal values of various physiological parameters (heart rate (HR), respiration rate (RR), body and skin temperatures) and their acclimatisation to a graded exercise load. The study was performed with a group of 6 pur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(22 citation statements)
references
References 19 publications
(54 reference statements)
2
9
2
Order By: Relevance
“…The walk speed was in line with the reference values for horses, the trot speed was in the lower range of the reference values for this gait and the canter speed was below the reference values [ 12 , 22 ]. Our previous study [ 19 ] on adult Lipizzan horses during lunging likewise demonstrated slower gaits than in horses during riding [ 23 , 24 ]. This could be a characteristic of Lipizzans or caused by the movement in a circle during lunging, which could have caused a less efficient combination of stride frequency and length than with a straightforward movement [ 12 ].…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…The walk speed was in line with the reference values for horses, the trot speed was in the lower range of the reference values for this gait and the canter speed was below the reference values [ 12 , 22 ]. Our previous study [ 19 ] on adult Lipizzan horses during lunging likewise demonstrated slower gaits than in horses during riding [ 23 , 24 ]. This could be a characteristic of Lipizzans or caused by the movement in a circle during lunging, which could have caused a less efficient combination of stride frequency and length than with a straightforward movement [ 12 ].…”
Section: Discussionmentioning
confidence: 95%
“…The reaction of HR to exercise is a function of work intensity and reflects the metabolic performance of horses. It is under the influence of various external and internal factors, including environmental conditions, fitness and health status of the horse [ 14 , 17 , 19 , 30 ]. The mean HRs in Lipizzan fillies BEx were above the physiological range for warm-blooded horses [ 12 , 19 , 26 , 28 , 31 ], with the highest value measured at ExT-1.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations